Myeloid-Specific Acly Deletion Alters Macrophage Phenotype In Vitro and In Vivo without Affecting Tumor Growth - de Goede, Kyra E. (Cancers (Basel), 2021)
SIMPLE SUMMARY: Tumor cells show different metabolism compared to normal tissue. For instance, they increase ATP-citrate lyase (Acly) expression for increased proliferation. Acly is therefore currently being targeted for cancer therapy. However, targeting this enzyme may have side effects on other cells within the tumor microenvironment, including tumor-associated macrophages (TAMs) which are immune cells crucial for cancer progression. As Acly deletion previously showed increased pro-inflammatory responses of macrophages in vitro, we hypothesized that Acly-deficient TAMs may better control tumor growth. Here, we determined the effect of Acly deficiency specifically in pro-cancer anti-inflammatory macrophages and TAMs in two mouse models of cancer. While Acly is crucial for anti-inflammatory macrophage activation, Acly-deficient TAMs do not affect tumor growth. Together, our results indicate that targeting Acly as anti-cancer therapy has no adverse effects on TAMs. ABSTRACT: Cancer cells rely on ATP-citrate lyase (Acly)-derived acetyl-CoA for lipid biogenesis and proliferation, marking Acly as a promising therapeutic target. However, inhibitors may have side effects on tumor-associated macrophages (TAMs). TAMs are innate immune cells abundant in the tumor microenvironment (TME) and play central roles in tumorigenesis, progression and therapy response. Since macrophage Acly deletion was previously shown to elicit macrophages with increased pro- and decreased anti-inflammatory responses in vitro, we hypothesized that Acly targeting may elicit anti-tumor responses in macrophages, whilst inhibiting cancer cell proliferation. Here, we used a myeloid-specific knockout model to validate that absence of Acly decreases IL-4-induced macrophage activation. Using two distinct tumor models, we demonstrate that Acly deletion slightly alters tumor immune composition and TAM phenotype in a tumor type-dependent manner without affecting tumor growth. Together, our results indicate that targeting Acly in macrophages does not have detrimental effects on myeloid cells.